Proteolytic Degradation of Amyloid β-Protein - Saido, Takaomi (Cold Spring Harbor Laboratory Press, 2012)
The amyloid β-protein (Aβ) is subject to proteolytic degradation by a diverse array of peptidases and proteinases, known collectively as Aβ-degrading proteases (AβDPs). A growing number of AβDPs have been identified, which, under physiological and/or pathophysiological conditions, contribute significantly to the determination of endogenous cerebral Aβ levels. Despite more than a decade of investigation, the complete set of AβDPs remains to be established, and our understanding of even well-established AβDPs is incomplete. Nevertheless, the study of known AβDPs has contributed importantly to our understanding of the molecular pathogenesis of Alzheimer disease (AD) and has inspired the development of several novel therapeutic approaches to the regulation of cerebral Aβ levels. In this article, we discuss the general features of Aβ degradation and introduce the best-characterized AβDPs, focusing on their diverse properties and the numerous conceptual insights that have emerged from the study of each.